Measurement of high temperature sensitivity of Al/(Zn:Cd:Ni:TiO2)/p-Si structure based on capacitance/conductance-voltage (C/G-V) - Bengi, Seda; Yeriskin, Seckin Altindal; Khalkhali, Arezou; Dere, Aysegul; Yildiiz, Kevser; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2025)
In this work, a cryogenic metal oxide diode temperature sensor has been fabricated using ZnCdNi:TiO2 metal oxide semiconductor on p-type silicon substrate for thermal sensor applications. The temperature sensing performance and fundamental electrical properties of Al/(ZnCdNi:TiO2)/p-Si were investigated using temperature dependent impedance measurements. There are two linear areas for low and high temperatures in the temperature sensitivity (S) for the fixed capacitance driver mode. The highest S value of 8.3 mV K-1 at 0.10 nF was obtained at high temperatures. The capacitance/conductance values were demonstrated to be considerably affected by voltage and temperature, particularly at accumulation and depletion regimes. The reverse bias 1/C-2-V characteristic was used to compute certain basic electrical parameters, including barrier height (Phi(B)), diffusion potential (V-D), and density of acceptor atoms (N-A) for each temperature. The resistance (R-i) values were calculated using the Nicollian-Brews method. Additionally, c(2) values were used to derive density of surface states (N-SS) values. Al/(ZnCdNi:TiO2)/p-Si's excellent quality and performance are further demonstrated by its low R-S values and suitable N-SS size. Furthermore, low Arrhenius plot activation energy values (E-a) suggest that the trapped electron either hops between traps or that the conduction band predominates. Al/(Zn:Cd:Ni:TiO2)/p-Si's suitability as thermal sensors both in low and high temperature regions supported by the variations in electrical characteristics and high S value.
Keywords: ZnCdNi:TiO2 thin film; temperature and voltage dependence; electrical parameters; series resistance and surface states; temperature sensitivity; Arrhenius plots